Impact of media on social behavior of individuals living in Karachi - Imtiaz, Fauzia; Ellahi , Noor; Zaidi, Yawar Hasan (International Journal of Endorsing Health Science Research, 2015)
Background: Today the world is known as a global village where information is easily accessible. Media plays a vital role in providing information, education and entertainment to the population. Media updates people about the current situations through their news channels which are providing the most up to date news within no time through live evidences and substantiations. Several studies have proved the impact of media directly on the acute stress response to collective trauma. Media coverage of collective traumas may trigger sociological distress in individuals outside the directly affected community. Objective: To determine the effect of media on Social behavior of the population of Karachi. Methodology: It’s a cross sectional questionnaire based study conducted in different areas of Karachi during, November 2014 to Feb 2015. The questionnaire includes demographic information, the type of media used for obtaining information and the impact of news on the social life of individuals. Results: Among the participants 46.6% were males and 53.4% were females. Television is the type of media that was used by most (442) of the population. Results showed that 31.9% showed no effect on their social life whereas 24.4% avoided the place/public transport for a few days, 18.6% didn’t go out at night, 17.3 avoided travelling alone and 7.8% of participants were afraid to go out. Conclusion: Television is the source of information for most people, beside the exaggeration in telecasting the news continues their work. Their social life is not affected anymore which causes them to become immune to the environment they are facing people.